207k views
1 vote
6c - (3 – 3c) = 24
Solve equation step by step

User Dimple
by
5.9k points

2 Answers

6 votes

Answer:

c = 3

Explanation:

6c - (3 – 3c) = 24

Distribute the minus sign

6c - 3 +3c = 24

Combine like terms

9c -3= 24

Add 3 to each side

9c-3+3 = 24+3

9c = 27

Divide each side by 9

9c/9 = 27/9

c = 3

User Carl Papworth
by
5.0k points
5 votes

Hi there! :)


\large\boxed{c = 3}

6c - (3 - 3c) = 24

Distribute the negative sign with terms inside the parenthesis;

6c - (3) - (-3c) = 24

6c - 3 + 3c = 24

Combine like terms:

9c - 3 = 24

Add 3 to both sides:

9c = 27

Divide both sides by 9:

c = 3.

User Thecarisma
by
5.2k points